In Hospital Outcome of Sars Cov-2 Infection Among Systemic Lupus Erythematosus Patients on Disease Modifying Drugs (Journal of Dhaka Medical College, 2023)
Background: COVID-19 is associated with hyperinflammatory syndrome causing worsening of disease severity. SLE is a rare autoimmune disease. Concomitant presence of both diseases may worsen COVID-19.Objective: To characterize patients with Systemic Lupus Erythematosus (SLE) affected by COVID- 19 and to observe medications on COVID-19 outcomes.Methodology: SLE with confirmed COVID-19 patients on Hydroxychloroquine admitted in COVID dedicated hospital in Dhaka was included. Data were prospectively collected via a structured questionnaire form and review of medical records. Only hospital outcomes were observed.Results: Total 17 patients were included, 11 of them had only SLE, 5 had lupus nephritis and only 1 had CNS lupus. All of them had confirmed COVID-19 detected by RT-PCR. 17 (100%) were taking immunomodulator (Hydroxychloro-quine), 7 (41.2%) steroids, 5 (29.4%) taking Mycophenolate mofetil before having COVID-19. Eleven (64.7%) of them had mild to moderate severity where 4 (23.5%) had severe & 2 (11.8%) had critical conditions. Of those 17 patients, 11 required supplemental oxygen (64.7%) during hospitalization, 2 (11.8%) admitted into ICU and required mechanical ventilation. Fifteen of them were discharged after 11 days (minimum 9, maximum 21) where 2 (11.8%) died due to hypoxic respiratory failure. Seven patients out of eleven who required supplemental oxygen were on prednisolone before illness only suffered mild to moderate illness.Conclusion: Previous intake of immunosuppressants like Hydroxychloroquine & Mycophenolate mofetil before admission to hospital did not seem to influence the severity of infection.J Dhaka Med Coll. 2021; 29(1): 94-98